Nano-functionalization and evaluation of antimicrobial activity of Tinospora cordifolia against the TolB protein of Pseudomonas aeruginosa – An antibacterial and computational study - Nath, Himporna; Khataniar, Ankita; Bania, Kusum K.; Mukerjee, Nobendu; Al-Hussain, Sami A.; Zaki, Magdi E. A.; Rajkhowa, Sanchaita (Frontiers in Microbiology, 2023)
Introduction Antibacterial drug resistance, brought on by the overuse of antibiotics, is one of the biggest threats to human health. It is crucial to consider cutting-edge strategies, such as herbal remedies, to control multidrug-resistant (MDR) bacteria. Methods This study evaluated the phytochemical, antioxidant and antibacterial properties of the various Tinospora cordifolia extracts. Functionalization of the isolated active compound was done using gold (Au) and silver (Ag) nanoparticles (NPs). Further, to understand the interaction of the isolated class, Cordifolisides, with its target, various in-silico methods were used. Results and Discussion The plant was reported from the Charaideo district of Assam, whose methanolic stem extract showed the maximum activity towards the nosocomial pathogen Pseudomonas aeruginosa. Consequently, the active compound was isolated and characterized as belonging to the class Cordifoliside using NMR. The AuNPs and AgNPs functionalized isolates showed enhanced antimicrobial activity against P. aeruginosa compared to the unfunctionalized isolate. The most reactive compound, Cordifoliside C was determined using Density Functional Theory (DFT) analysis, whose interactions with the TolB protein were studied using molecular docking methods, which revealed good binding interactions of Cordifoliside C with the TolB protein. Conclusion This study offers enormous potential for drug design and might be used as a pipeline to address the urgent problem of multidrug-resistance in bacteria. Graphical Abstract